The tale of Benjamin Bunny : with Peter Rabbit - Potter, Beatrix, 1866-1943. (New York : Little Simon, 1986)
Peter's mischievous cousin, Benjamin Bunny, persuades him to go back to Mr. McGregor's garden to retrieve the clothes he lost there.
"40 collector's stickers inside"--Cover.
Originally published in 1904 by F. Warne, New York.
Keywords: Rabbits -- Fiction